Effects of export duty structure on the performance of the Malaysian palm oil industry - Wong, Kelly Kai Seng (Routledge, 2014)
This study examines the impact of the abatement of the export duty on the Malaysian palm oil industry performance. The simulation results show that the impact of reductions in the export duty rates and the impact of increases in the threshold prices on the Malaysian palm oil industry have the same impact but with different magnitudes. Even the simulated results indicate that the policy of further reductions in the Malaysian export duty will promote its positive effects on the local palm oil industry; however, the impact is shown to not be significant. The further reduction of the export tax is very constrained and believed to no longer be the most effective policy in enhancing the competitiveness of local palm oil industry in the future. Hence, policymakers have to be aware of the possibility that the reduction of the export tax may no longer be an effective sustainable approach in facilitating the development of Malaysian palm oil industry.